Too similar or too different: Effect of acculturation strategies on judgments of a violent act committed by a Vietnamese offender. (July 2020) - Taillandier-Schmitt, Anne; Combalbert, Nicolas
Abstract: In the literature, several studies have shown that the perpetrator's ethnic origin and acculturation strategy are particularly influential extrajudicial factors, but authors have focused on highly stigmatized groups. The aim of this study was to examine how the participants' judgments were influenced by the acculturation strategy of a Vietnamese aggressor (member of a valued minority group in France), the consequences of the act for the victim, and their level of SDO. It was expected that assimilation, which reflects a strong similarity with the majority group, or separation, reflecting strong dissimilarity, would lead to negative judgments of the assault and its perpetrator and a harsher punishment. After reading a scenario describing a physical assault committed by a Vietnamese man, in which the perpetrator's acculturation strategy and the consequences of the act were manipulated, 196 French students completed a questionnaire. The results confirm our hypothesis. Moreover, they show that when there were serious consequences for the victim, the act was considered to be more serious if the offender had not adopted French culture. However, when the consequences were minor, the act was considered to be more serious and a harsher punishment was recommended if the offender had adopted French culture. We explain how acculturation strategy is an important factor when judging transgressions, and how being too similar or too different to the majority group can increase the perceived threat. The status of SDO is discussed.